Performance Guaranteed Traffic Signal Control with Frame-Based Algorithm - Wan, Xili; Zhao, Wentian; Guan, Xinjie; Ye, Feng; Bai, Guangwei (Annual IEEE Communications Society Conference on Sensor, Mesh and Ad Hoc Communications and Networks workshops (Print), 2018)
In urban area, fast growth in the number of vehicles has led to a series of traffic problems, including traffic jams,high traffic accident rates, etc. Efficient traffic signal control methods has been shown to be an essential way to significantly mitigate traffic problems. In this poster, different from previous online methods, we propose a frame-based model and an efficient algorithm to solve the drawbacks of online algorithm by scheduling the vehicles that have accumulated at the intersection over a period of time. Preliminary experiments exhibit that the proposed algorithm could greatly improve the throughput of the intersection.